Reach and Operating Time Correction of Digital Distance Relay - A N Sarwade; P K Katti; J G Ghodekar (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Current and voltage signals recieved from conventional iron core Current Transformer (CT) and Voltage Transformer plays very important role for correct operation of Distance Distance Relay (DDR). Increase in secondary burden connected to CT causes it to saturate at earlier stage. The saturated CT produces distorted secondary current, causing DDR to under reach and to operate by certain time delay. Rogowski Coils (RCs) are attaining increased acceptance and use in electrical power system due to their inherent linearity, greater accuracy and wide operating current range. This paper presents use of RC as an advanced measurement device suitable for DDR. Case study for validation of use of RC is carried out on low voltage system. The simulation results of Distance protection scheme used for protection of part of 220kV AC system shows excellent performance of RC over CT under abnormal conditions.